2010
DOI: 10.1038/pj.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensionally extended organic high-spin poly(aminium cationic radical)s and their magnetic force microscopic images

Abstract: Purely organic high-spin poly(aminium cationic radical)s of two-dimensionally extended soluble aromatic polyamines P1 and P2 were prepared by the palladium-catalyzed polycondensation of two multifunctional monomers, followed by chemical or electrochemical oxidations. The chemical structures of the precursor polyamines were fully characterized by 1 H-and 13 C nuclear magnetic resonance (NMR), infrared and MALDI-TOF mass spectra (MS). The aminium radical sites of N,N,N¢,N¢-tetraaryl-pphenylenediamines were conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Thus, the first oxidation of P4 was caused by the triphenylamine units. The observed potential is consistent with previous reports of similar triphenylamine polymers …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the first oxidation of P4 was caused by the triphenylamine units. The observed potential is consistent with previous reports of similar triphenylamine polymers …”
Section: Resultssupporting
confidence: 93%
“…The observed potential is consistent with previous reports of similar triphenylamine polymers. [27][28][29][30] The redox activity of the selected P2 and P4 samples was also investigated by spectroelectrochemistry. When the potential of 1.5 V was applied to the polymer fi lms, their absorption peak intensities gradually decreased ( Figure S5, Supporting Information).…”
Section: Electrochemistrymentioning
confidence: 99%
“…The E ox values suggested that the triphenylamine derivatives are stronger donors than the fluorene unit and that the substitution of the methoxy group at the para-position with respect to the nitrogen atom facilitated the oxidation, whereas the cyano group substitution made it more difficult. This result is consistent with the redox behavior of the reported triphenylamine oligomers and polymers without the DPP unit [29][30][31][32][33]. In contrast, the E red values originating from the DPP unit were not affected by the electron-donating comonomer structures.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 81%
“…[2][3][4][5] For example, the addition of p-type doping reagents, such as tetracyanoethylene, 7,7,8,8-tetracyanoquinodimethane (TCNQ) and their derivatives, to electron-rich polymers produces open-shell polymers because of the charge-transfer (CT) complexation. [6][7][8][9][10] However, a similar approach using the combination of n-type doping reagents and electrondeficient polymers is rare, probably because of the difficulty of preparing precursor polymers, namely electron-deficient conjugated polymers, and the limited chemical stability of the n-doped polymers at room temperature.…”
Section: Introductionmentioning
confidence: 99%